2012
DOI: 10.1016/j.neuron.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillations Are Generated Locally in an Attention-Related Midbrain Network

Abstract: Gamma-band (25–140 Hz) oscillations are a hallmark of sensory processing in the forebrain. The optic tectum (OT), a midbrain structure implicated in sensorimotor processing and attention, also exhibits gamma oscillations. However, the origin and mechanisms of these oscillations remain unknown. We discovered that in acute slices of the avian OT, persistent (>100ms) epochs of large amplitude gamma oscillations can be evoked that closely resemble those recorded in vivo. We found that cholinergic, glutamatergic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 56 publications
(90 reference statements)
4
60
0
Order By: Relevance
“…Responses to sensory stimuli in the intermediate/deep layers of the OT are highly context dependent (Frost and Nakayama 1983;Mysore et al 2010Netser et al 2011;Reches and Gutfreund 2008;Woods and Frost 1977;Zahar et al 2009). Neurons in these layers express a variety of cholinergic, glutamatergic, and GABAergic receptors (Goddard et al 2012;Luksch 2003;Sorenson et al 1989), suggesting a rich background for neural modulations. Studies have reported that priming by microstimulation or sensory stimulation can modulate behavioral and neural responses in the OT Winkowski and Knudsen 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to sensory stimuli in the intermediate/deep layers of the OT are highly context dependent (Frost and Nakayama 1983;Mysore et al 2010Netser et al 2011;Reches and Gutfreund 2008;Woods and Frost 1977;Zahar et al 2009). Neurons in these layers express a variety of cholinergic, glutamatergic, and GABAergic receptors (Goddard et al 2012;Luksch 2003;Sorenson et al 1989), suggesting a rich background for neural modulations. Studies have reported that priming by microstimulation or sensory stimulation can modulate behavioral and neural responses in the OT Winkowski and Knudsen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that priming by microstimulation or sensory stimulation can modulate behavioral and neural responses in the OT Winkowski and Knudsen 2007). Moreover, gamma band network oscillations can be recorded in the LFP and in multiunit signals in the OT (Goddard et al 2012;Neuenschwander et al 1996;Sridharan et al 2011). The amplitude of these gamma oscillations has been suggested to relate to internal states such as spatial attention.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the oscillations arise in the motor layers of the tectum and the frequency is determined by local GABAergic circuits, which in turn, through their cholinergic inputs to the visuosensory layers, are responsible for generating the oscillations in activity of the neurons in the visuosensory layer (Goddard et al 2012, King 1990). …”
Section: Microcircuits Of the Superior Colliculusmentioning
confidence: 99%
“…Recently, the ability of this brainstem network to generate gamma frequency oscillations like those recorded in the cerebral cortex associated with attention was reported in a slice preparation of the avian brain (Goddard et al 2012). The results suggest that the oscillations arise in the motor layers of the tectum and the frequency is determined by local GABAergic circuits, which in turn, through their cholinergic inputs to the visuosensory layers, are responsible for generating the oscillations in activity of the neurons in the visuosensory layer (Goddard et al 2012, King 1990).…”
Section: Microcircuits Of the Superior Colliculusmentioning
confidence: 99%
See 1 more Smart Citation